Efficient Conduction in Thin Film Transistors Consisting of Colloidal Nanocrystals: Effect of Nanocrystal Geometry. Issue 12 (28th September 2018) - Wee, Hansol; Yu, Ji Woong; Ryu, Ji Ho; Ghosh, Abhijit; Lee, Won Bo
Abstract: Conducting nanocrystals (NCs) are effective components of thin film electronic devices. Devices consisting of spherical nanocrystals have been proven to be suitable components of such devices owing to their easy dispersity. However, complex geometries of the NCs and suitably controlled dispersion can facilitate large scale synthesis by reducing the requisite density of nanocrystals at the threshold of conduction. Here, simulation results are reported exploring different NC geometries. The results show that the conduction threshold is lowered depending on the complexity of the NC geometry. The effective interaction between the NCs is quantified by measuring the structure factor. The results are interesting from the synthesis point of view. Abstract : Improvement of a thin film transistor by tuning the colloidal nanocrystal geometry dispersed in it has been gaining popularity recently, while the systematic study about how such a modification affects the conduction is rather sparsely investigated. Here, how the manipulation of branched nanocrystal in both size and geometry changes percolation, using Langevin dynamics and cluster analysis, is presented.